2015
DOI: 10.1111/1750-3841.12782
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life Determination of Sliced Portuguese Traditional Blood Sausage—Morcela de Arroz de Monchique through Microbiological Challenge and Consumer Test

Abstract: Morcela de Arroz (MA) is a ready-to-eat blood and rice cooked sausage produced with pork, blood, rice, and seasonings, stuffed in natural casing and cooked above 90 °C/30 min. It is commercialized whole, not packed, with a restricted shelf life (1 wk/0 to 5 °C). The objective of this work was to establish sliced MA shelf life considering both the behavior of L. monocytogenes through a microbiological challenge test (MCT) and the consumer acceptability of MA stored: vacuum packed (VP), modified atmosphere packe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…occurred after production, possibly during slicing or packaging. The shelf-life of sliced blood sausage is several days to a few weeks (34) and the amount of L. monocytogenes found in unopened blood sausage samples was below the limit of 100 CFU/g. Storage beyond the anticipated shelf-life or insufficient refrigeration might have allowed L. monocytogenes to multiply inside the vehicle, which would only be prevented by a zero-tolerance policy.…”
Section: Discussionmentioning
confidence: 99%
“…occurred after production, possibly during slicing or packaging. The shelf-life of sliced blood sausage is several days to a few weeks (34) and the amount of L. monocytogenes found in unopened blood sausage samples was below the limit of 100 CFU/g. Storage beyond the anticipated shelf-life or insufficient refrigeration might have allowed L. monocytogenes to multiply inside the vehicle, which would only be prevented by a zero-tolerance policy.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of adequacy might occur due to microbial, chemical, and/or physical modifications that result in detectable sensory traits recognized as spoilage and/or loss of the safety status of the product (Vorst et al, ). Chicken breast might be contaminated with pathogens (Pulido‐Landínez, ; Ricke et al, ); however, as it is not a ready‐to‐eat product, microbial safety is not a major concern when defining its shelf life (Pereira, Silva, Matos, & Patarata, ). Moreover, it has been demonstrated that pathogens do not compete well with the spoilage microbiota of fresh meat during storage (EFSA BIOHAZ Panel, ).…”
Section: Introductionmentioning
confidence: 99%
“…A challenge test was performed to study the behavior of L. monocytogenes during the storage of sliced cured pork loins, as described in the literature [16]. Freshly manufactured samples were obtained from the industry and were contaminated with a mixture of four strains of the pathogen: one strain from a culture collection (ATCC 35152), and three strains previously isolated from meat product industrial environments (laboratory collection).…”
Section: Challenge Test With Listeria Monocytogenesmentioning
confidence: 99%
“…The hurdles used to achieve that reduction might include chemical preservatives, mild heat treatments, and drying [15]. Increases in demand for easy-to-use meat products and the opportunity to purchase smaller portions [16] has been driving the industry to introduce a final step of slicing the cured loins and packaging smaller portions. Slicing is always a sensitive step in the industry.…”
Section: Introductionmentioning
confidence: 99%